2007
DOI: 10.1093/icesjms/fsm075
|View full text |Cite
|
Sign up to set email alerts
|

Diel variation in the vertical distribution and schooling behaviour of sardine (Sardina pilchardus) off Portugal

Abstract: Zwolinski, J., Morais, A., Marques, V., Stratoudakis, Y., and Fernandes, P. G. 2007. Diel variation in the vertical distribution and schooling behaviour of sardine (Sardina pilchardus) off Portugal. – ICES Journal of Marine Science, 64: 963–972. Diel patterns in the schooling behaviour and vertical distribution of pelagic fish schools were studied by examining their echotraces from repeated acoustic survey transects at three inshore sites off the Portuguese coast. At two sites, sardine was the dominant pelagic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 40 publications
2
27
0
9
Order By: Relevance
“…Such formations presuppose collective behavior patterns that are mainly based on the interactions of individuals, which in turn depend on a complex sum of sensory stimuli (Weissburg & Browman 2005). Such collective behavior during spawning was shown by means of egg and acoustic sampling data for the Atlantic sardine stock by Zwolinski et al (2006Zwolinski et al ( , 2007. Therefore, even if buoyancy is af fected by pregnancy and spawning individuals are forced to move offshore and downwards to spawn, the formation of massive and functional social structures that ensure spawning success through enhancing fertilization rates and progeny survival would also require intra-and intersexual interaction among individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such formations presuppose collective behavior patterns that are mainly based on the interactions of individuals, which in turn depend on a complex sum of sensory stimuli (Weissburg & Browman 2005). Such collective behavior during spawning was shown by means of egg and acoustic sampling data for the Atlantic sardine stock by Zwolinski et al (2006Zwolinski et al ( , 2007. Therefore, even if buoyancy is af fected by pregnancy and spawning individuals are forced to move offshore and downwards to spawn, the formation of massive and functional social structures that ensure spawning success through enhancing fertilization rates and progeny survival would also require intra-and intersexual interaction among individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The same authors found, using acoustic sampling, that the mature sardines that contributed to the spawning of these egg cohorts were located at 60 m depth. Zwolinski et al (2007) suggested that large shoals of actively spawning sardines are formed in close association to the seabed around the hours of spawning.…”
Section: Introductionmentioning
confidence: 99%
“…Time of sampling is among the main factors that could cause bias in the haul catch. The bias could be even more pronounced in small pelagics, mainly because they are known to show diel vertical migration, form dense schools during daytime, and disperse at loose aggregations close to the surface during night-time (Woodhead 1966, Massè 1996, Giannoulaki et al 1999, Zwolinski et al 2007, Tsagarakis et al 2012. Time of fishing might also be related to trawl selectivity, increasing the possibility for the smaller individuals to escape from the net during the daytime because of the optical contact with the trawl and the large mesh size of the net at the front of the gear, while the absence of this contact during the night-time supports "blind", random selection sampling.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of the time of day on acoustic and biological data sampling is an issue that has raised several contradictions regarding the introduction of error in abundance estimates (Iglesias et al 2003, Zwolinski et al 2007. The latter largely depends on parameters related to species behaviour.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation